2016
DOI: 10.1007/s10072-016-2648-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of carotid intima-media thickness in children with migraine: a marker of subclinical atherosclerosis

Abstract: Migraine is a commonly seen neurovascular disorder during childhood. Inflammation induced by the activation of cytokines and neuropeptides is implied in its pathophysiology. There is an association between inflammation and atherosclerosis in patients with migraine. In addition, there is a strong correlation between early atherosclerotic wall lesions and carotid intima-media thickness (CIMT). The study population consisted of 57 migraine patients aged 5-17 years, as well as 47 healthy children who served as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Several other vascular risk factors have been reported as associated with migraine: experimental hypoxia (100); altered brachial and femoral artery compliance as well as decreased brachial artery diameter (41); increased carotid artery media thickness, a subclinical marker of early atherosclerosis (43, 44), has been reported as heightened in pediatric migraineurs (45) and adult migraineurs (42). Migraineurs (particularly women) with MA have two times the risk of ischemic stroke (38), and MA and migraine in general, in an unadjusted population-based analysis, have been associated with stroke, myocardial infarction and claudication (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other vascular risk factors have been reported as associated with migraine: experimental hypoxia (100); altered brachial and femoral artery compliance as well as decreased brachial artery diameter (41); increased carotid artery media thickness, a subclinical marker of early atherosclerosis (43, 44), has been reported as heightened in pediatric migraineurs (45) and adult migraineurs (42). Migraineurs (particularly women) with MA have two times the risk of ischemic stroke (38), and MA and migraine in general, in an unadjusted population-based analysis, have been associated with stroke, myocardial infarction and claudication (34).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated vascular risk factors have been found in migraineurs, including vasoactive plasma endothelin (ET-1), a marker for atherosclerosis and endothelia injury (42). Increased carotid artery media thickness, a subclinical marker of early atherosclerosis (43, 44), has been reported as heightened in pediatric migraineurs (45) and in adult migraineurs (42). …”
Section: Introductionmentioning
confidence: 99%
“…In migraineurs with subclinical infarction in the CAMERA study, the clinical and radiological features of the multiple, small lesions found predominantly in the deep arterial border zone of the cerebellum suggested hypoperfusion or embolism rather than atherosclerosis 38 . In contrast, there are 7 studies reporting evidence of subclinical atherosclerosis in adults with migraine, 136‐142 including in those with episodic migraine and those with aura 136‐139 . One recent study also reported an independent association of carotid wall thickening with triptan and ergotamine consumption, suggesting that repeated use of these vasoconstrictive agents may have lasting effects 137 .…”
Section: Potential Mechanisms Of Migraine‐related Strokementioning
confidence: 96%
“…A 2019 meta‐analysis of ultrasonic assessment of CIMT in participants from 7 studies reported significantly greater CIMT in patients with migraine compared to controls, but no differences in CIMT between patients with MWA and controls, or MWoA and controls 140 . This analysis included 2 studies of children showing increased CIMT in migraine, even when of recent onset 141,142 …”
Section: Potential Mechanisms Of Migraine‐related Strokementioning
confidence: 99%
“…Several studies have investigated these mechanisms in migraine and obesity [4][5][6] . Some adult and pediatric studies have showed the link between migraine and vascular events such as ischemic stroke and atherosclerosis as well 7,8 .…”
Section: Introductionmentioning
confidence: 99%